Lessons from the past: A window on the future - Katz, Alan; Brownell, Marni; Smith, Mark (International Journal of Population Data Science, 2018)
Introduction The Manitoba Centre for Health Policy has provided international leadership in organizing and accessing administrative databases, linking and analyzing data and translating the findings of research into policy for three decades. During this period, MCHP has addressed numerous challenges in each of these areas. Objectives and Approach Linked data research is expanding rapidly in terms of access to new data sources, different types of data, sharing of data across jurisdictions, and advances in data analytics. Technical advances such as computing power and artificial intelligence support these developments while governance structures and ethical issues challenge them. This presentation will describe some of the challenges MCHP has met with a view to gaining insight into how solutions evolved and how experience can guide the future of linked data research. Results The scaling up of linked data research will need to address specific challenges including de-identification of free text, accessing and linking data from private enterprise such as wearables, and interdisciplinary collaboration to incorporate new techniques developed by computer scientists. Cross-jurisdictional data analysis presents challenges in addressing differences in data architecture. Inter-jurisdictional and international data sharing create ethical and governance challenges. Experience has demonstrated the critical role that relationship building plays in addressing each of these. These relationships are different depending on the partners. They are all based on the development of common use of language, understanding the motivation and concerns of each party, clearly articulating the benefits of the relationship and data use and attention to the cultural and political environment. Conclusion/Implications Lessons from the past can guide us in addressing challenges posed by the exciting opportunities available to us all. While many of these challenges will be solved with technical solutions, we should not overlook the importance of human relationships in building a culture of trust and collaboration as we move